2020
DOI: 10.1098/rsta.2019.0593
|View full text |Cite
|
Sign up to set email alerts
|

Learning automata based energy-efficient AI hardware design for IoT applications

Abstract: Energy efficiency continues to be the core design challenge for artificial intelligence (AI) hardware designers. In this paper, we propose a new AI hardware architecture targeting Internet of Things applications. The architecture is founded on the principle of learning automata, defined using propositional logic. The logic-based underpinning enables low-energy footprints as well as high learning accuracy during training and inference, which are crucial requirements for efficient AI with long operating life. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…These Boolean 119 features are also referred to as literals:X and X. Current research has shown that 120 significance-driven Booleanization of features for the Tsetlin Machine is vital in control-121 ling the Tsetlin Machine size and processing requirements [18]. Increasing the number of 122 features will increase the number of TA and increase computations for the clause module 123 and subsequently the energy spent in incrementing and decrementing states in the 124 feedback module.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…These Boolean 119 features are also referred to as literals:X and X. Current research has shown that 120 significance-driven Booleanization of features for the Tsetlin Machine is vital in control-121 ling the Tsetlin Machine size and processing requirements [18]. Increasing the number of 122 features will increase the number of TA and increase computations for the clause module 123 and subsequently the energy spent in incrementing and decrementing states in the 124 feedback module.…”
mentioning
confidence: 99%
“…Audio data streams are always subject to redundancies in the channel that formal-156 ize as nonvocal noise, background noise and silence [20,21]. Therefore the challenge [18].…”
mentioning
confidence: 99%
See 3 more Smart Citations